Auditory self-motion simulation is facilitated by haptic and vibrational cues suggesting the possibility of actual motion - Riecke, Bernhard E.; Feuereissen, Daniel; Rieser, John J (ACM Transactions on Applied Perception (TAP), 2009)
Sound fields rotating around stationary blindfolded listeners sometimes elicit auditory circular vection, the illusion that the listener is physically rotating. Experiment 1 investigated whether auditory circular vection depends on participants' situational awareness of “movability,” that is, whether they sense/know that actual motion is possible or not. While previous studies often seated participants on movable chairs to suspend the disbelief of self-motion, it has never been investigated whether this does, in fact, facilitate auditory vection. To this end, 23 blindfolded participants were seated on a hammock chair with their feet either on solid ground (“movement impossible”) or suspended (“movement possible”) while listening to individualized binaural recordings of two sound sources rotating synchronously at 60°/s. Although participants never physically moved, situational awareness of movability facilitated auditory vection. Moreover, adding slight vibrations like the ones resulting from actual chair rotation increased the frequency and intensity of vection. Experiment 2 extended these findings and showed that nonindividualized binaural recordings were as effective in inducing auditory circular vection as individualized recordings. These results have important implications both for our theoretical understanding of self-motion perception and for the applied field of self-motion simulations, where vibrations, nonindividualized binaural sound, and the cognitive/perceptual framework of movability can typically be provided at minimal cost and effort.
Keywords: Riecke; Riecke_2009; artificial, augmented, and virtual realities; auditory vection; bernhard-riecke; circular vection; daniel-feuereissen; iSpaceWeb; john-rieser; journalPaper; multi-modal vection; vection